Comparison of saliva and oro-nasopharyngeal swab sample in the molecular diagnosis of COVID-19 - Güçlü,Ertuğrul (2020)
SUMMARY BACKGROUND Healthcare personnel are at risk of becoming infected while taking upper and/or lower respiratory tract specimens. Therefore, there is a need for sampling methods that do not risk infecting them. In this study, we aimed to compare the saliva and Oro-Nasopharyngeal Swab (ONS) sampling methods. METHODS Patients were divided into three groups. Group 1 included patients whose diagnosis of COVID-19 was confirmed by polymerase chain reaction (PCR). Group 2 included patients with COVID-19 compatible findings in lung computed tomography (CT), but with a negative PCR. Group 3 included patients who presented to the emergency department with COVID-19 compatible complaints but had normal CT. Saliva and ONS samples were taken on the third day of hospitalization in groups 1 and 2, whereas in group 3, they were taken at the time of admission to the hospital. RESULTS A total of 64 patients were included in the study. The average age was 51.04 ± 17.9 years, and 37 (57.8%) were male. SARS-CoV-2 was detected in 27 (42.2%) patients’ saliva samples. While the sensitivity and positive predictive value of saliva samples were 85.2%, specificity and negative predictive value were 89.2%. The value of kappa was in substantial agreement (0.744), and it was found statistically significant (<0.001). CONCLUSIONS Saliva samples can be used instead of ONS samples in detecting SARS-CoV-2. Investigating SARS-CoV-2 with saliva is cheaper, easier for the patient and overall, and, most importantly, it poses much less risk of SARS-CoV-2 contamination to healthcare personnel.